2019
DOI: 10.18632/oncotarget.26588
|View full text |Cite
|
Sign up to set email alerts
|

High CXCR4 expression impairs rituximab response and the prognosis of R-CHOP-treated diffuse large B-cell lymphoma patients

Abstract: Survival of diffuse large B-cell lymphoma (DLBCL) patients has improved by inclusion of rituximab. Refractory/recurrent disease caused by treatment resistance is, however, a major problem. Determinants of rituximab sensitivity are not fully understood, but effect of rituximab are enhanced by antagonizing cell surface receptor CXCR4. In a two-step strategy, we tested the hypothesis that prognostic value of CXCR4 in DLBCL relates to rituximab treatment, due to a hampering effect of CXCR4 on the response of DLBCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
(64 reference statements)
3
21
0
Order By: Relevance
“…Yuan et al showed that high microRNA-125b and microRNA-130a levels in the serum of DLBCL cases are associated with R-CHOP resistance in DLBCL cases (Yuan et al, 2016). Laursen et al showed that high expression of CXCR4 on the tumor cell surface may be responsible for R-CHOP resistance in a subset of DLBCL cases (Laursen et al, 2019). Another study by Wilson et al asked whether ABC DLBCL patients who have chemotherapy refractory disease can be treated through inhibition of BCR signaling.…”
Section: Chemotherapy Resistance-associated Genetic Aberrations In B mentioning
confidence: 99%
“…Yuan et al showed that high microRNA-125b and microRNA-130a levels in the serum of DLBCL cases are associated with R-CHOP resistance in DLBCL cases (Yuan et al, 2016). Laursen et al showed that high expression of CXCR4 on the tumor cell surface may be responsible for R-CHOP resistance in a subset of DLBCL cases (Laursen et al, 2019). Another study by Wilson et al asked whether ABC DLBCL patients who have chemotherapy refractory disease can be treated through inhibition of BCR signaling.…”
Section: Chemotherapy Resistance-associated Genetic Aberrations In B mentioning
confidence: 99%
“…Independent validation across different cohorts is of great importance for biomarker development, and OSdlbcl is a web server that could facilitate the cross‐validation of the prognostic value of biomarkers across seven DLBCL cohorts. To determine the prognosis performance of OSdlbcl, we collected 23 previously published DLBCL prognostic factors at the mRNA or protein level and tested their prognostic power in OSdlbcl at the mRNA level (Table , Figure ) . The forest plots more effectively presented the comparison results from references and OSdlbcl (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the prognosis performance of OSdlbcl, we collected 23 previously published DLBCL prognostic factors at the mRNA or protein level and tested their prognostic power in OSdlbcl at the mRNA level (Table 2, Figure 1). 2,9,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The forest plots more effectively presented the comparison results from references and OSdlbcl ( Figure S1). Results showed that about 52% (12 out of 23) of biomarkers have significant prognostic values in the combined cohorts, while the remaining biomarkers (11 out of 23) present significant prognostic values in one or more cohorts ( Table 2).…”
Section: Evaluation Of Previously Reported Dlbcl Prognostic Biomarkmentioning
confidence: 98%
“…For all three genes, their implication in cancer surveillance has been demonstrated in more than 20 different solid cancer types [7][8][9]. Their role has also been investigated in DLBCL [10][11][12][13][14][15][16], however, these data are inconsistent and rather limited. We observed CXCR4 expression in non-neoplastic GC-B but a significantly higher expression in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…In solid cancer, abnormalities in the CXCR4-CXCL12-axis have been linked to many processes, including proliferation, survival, migration, invasion, and metastasis in solid cancer [7][8][9], thereby providing evidence for the importance of this chemokine signalling pathway in these malignancies. So far, we and other groups performed studies investigating the role of CXCR4 in DLBCL, whereby results mainly point towards a prominent role of CXCR4 in lymphoma dissemination [10][11][12][13][14][15][16]. However, data from these studies are to some extent inconsistent and limited.…”
Section: Introductionmentioning
confidence: 99%